Experience of handling beryllium, tritium and activated components from JET ITER like wall. (25th January 2016) - Widdowson, A; Baron-Wiechec, A; Batistoni, P; Belonohy, E; Coad, J P; Dinca, P; Flammini, D; Fox, F; Heinola, K; Jepu, I; Likonen, J; Lilley, S; et al.
Abstract: JET components are removed periodically for surface analysis to assess material migration and fuel retention. This paper describes issues related to handling JET components and procedures for preparing samples for analysis; in particular a newly developed procedure for cutting beryllium tiles is presented. Consideration is also given to the hazards likely due to increased tritium inventory and material activation from 14 MeV neutrons following the planned TT and DT operations (DTE2) in 2017. Conclusions are drawn as to the feasibility of handling components from JET post DTE2.